Internal Iliac Arteries Ligation An effective Method in the control of Pelvic Haemorrhage - Jabeen, Sadaqat (Journal of Postgraduate Medical Institute, 2011)
Internal iliac ligation was performed in 13 cases. Four amongst them were gynaecologic cases and rest were obstetrics. Obstetric cases included PPH, ruptured uteri, DIC extensive genital tract lacerations and atonic uteri; while gynaecological cases were of pelvic malignancy and tumours. Three deaths occured in this series but these weere not due to procedure itself. Two cases were in irreversible shock and one with acute renal failure. Other patients had ultimately an uneventful recovery.